METAPHORS AND ARGUMENTS TO SEMANTIC POLITICAL METAPHORS IN INDONESIAN MASS MEDIA AND ITS PERSUASIVE EFFECT TOWARD READERS - Yuli Widiana; Roro Arielia Yustisiana (Soegijapranata Catholic University, 2015)
The research is aimed to describe kinds of political metaphors and their metaphorical meanings. Furthermore, the persuasive effect of political metaphors in mass media toward the readers is also analyzed based on certain parameters. The pragmatic equivalent method and the referential equivalent method are applied to analyze the data. The kinds of political metaphors include metaphors with nature as a parable, metaphors with plants as a parable, metaphors with terms from various fields, metaphors with common things as a parable, metaphors with particular verbs, and metaphors with particular adjectives. The readers could comprehend political metaphors well although their interest in political news is low. Apparently, the persuasive effect of political metaphors on the public is high. It becomes a trigger for people to take action to create a better political atmosphere.